Preoperative coagulation abnormalities as a risk factor for adverse events after pancreas surgery. Issue 6 (22nd January 2018) - Castle, Joshua; Mazmudar, Aditya; Bentrem, David
Abstract : Objective: To determine whether elevated INR or PTT values predicted 30‐day postoperative adverse events following elective pancreatectomy. Methods: The American college of surgeons national surgical quality improvement program (ACS‐NSQIP) database was used to identify 14 747 patients undergoing elective pancreatectomy from 2005 to 2013. The association of elevated INR or PTT with 30‐day postoperative outcomes of morbidity and mortality was examined using multivariate logistic regression analysis. Results: The overall 30‐day mortality rate increased from 1.8% to 3.3% from the control to the high INR or PTT group ( P  = <0.001). An elevated INR/PTT increased the odds for bleeding requiring transfusion, superficial SSI, sepsis, unplanned intubation or >48 h on a ventilator, cardiac arrest or myocardial infarction, acute renal failure, return to the OR, and prolonged length of stay. With the exception of superficial SSI, multivariate logistic regression models revealed that these same events remained statistically significant after controlling for potential confounders. Conclusion: Prolonged bleeding times (high INR/PTT) is associated with increased mortality and adverse outcomes after pancreas surgery. A patient's coagulation profile may serve as a risk stratification tool to identify higher risk patients that require more resources.